Risk-return classes of Singapore equity unit trusts, 2002-2011. - Tan, Jin. (2013)
This study examines the performance of equity unit trusts that are available to the retail investors residing in Singapore, and whether its performance would persist in the future. These unit trusts may invest in Singapore or foreign equity markets. We collect return data on the equity unit trusts provided by Thomson Reuters Datastream, and computed its performance from 2002 to 2011. We use the return on Straits Times Index Exchange-Traded Fund (STI ETF) as the market benchmark. We discover that on average, returns on the equity unit trusts underperform the return on the STI ETF. This implies that investors are better off investing in STI ETF. We also find that the returns on winning equity unit trusts do not persist. This indicates that the strategy of investing in winners does not guarantee the same relative performance in the subsequent year.